Efforts To Improve Speaking Ability Of Xi Pplg 2 Using Genre Based Approach Assisted By Canva (psnppg, 2023)
This research aims to improve the speaking skills of class XI PPLG 2 students at SMK Negeri 2 Semarang using the Genre Based Approach assisted by Canva. Researchers focus on student problems that can be improved through applying an approach assisted by a media in narrative text material. This research was carried out over 2 cycles and in each cycle there were planning, implementation, observation, and reflection activities. This type of research is classroom action research which uses qualitative and quantitative methods. To obtain research results, researchers use data collection techniques such as observation, field notes, tests, and documents which function to store student recording results. The results of this research show an increase in students' speaking abilities from pre-cycle to cycle II. Where in the pre-cycle the average student score was 55.3, then in cycle I it was 60.06, and in cycle II it was 76.3. Based on the resulting data, it shows that research on the application of the Genre Based Approach assisted by Canva can improve students' speaking abilities.
Keywords: Speaking skill; Genre Based Approach; Narrative Text